Mathematic Model Design Of Solar Pumping For Drip Irrigation Systems - et. al., Mhamdi Hicham, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The use of solar energy in isolated sites for different applications, such as water pumping, is of primary interest to people in developing countries who do not have safe access to water drinking. But photovoltaic generators have two major drawbacks that are a low yield and a high blow. In order to increase the performance of these systems. Proper adaptation between the solar generator and the load reduces the cost of installation. The choice of an energy system must obey and comply with certain rules. The selected energy system must show as a preliminary its competitiveness with respect to other systems for the same rendered service. The present study have a propose the modeling, simulation, sizing and realization of a photovoltaic pumping system operating over the sun. This system consists of a set of interacting elements; namely the photovoltaic panels, the voltage inverter, the asynchronous motor, the centrifugal pump and the hydraulic circuit.